Androgen deprivation therapy for prostate cancer and risk of dementia. (6th February 2019) - Robinson, David; Garmo, Hans; Van Hemelrijck, Mieke; Damber, Jan‐Erik; Bratt, Ola; Holmberg, Lars; Wahlund, Lars‐Olof; Stattin, Pär; Adolfsson, Jan
Abstract : Objectives: To study whether androgen deprivation therapy (ADT), the mainstay treatment for advanced and disseminated prostate cancer, is associated with risk of dementia. Methods: Risk of dementia in men with prostate cancer primarily managed with ADT or watchful waiting (WW) in the Prostate Cancer Database Sweden, PCBaSe, was compared with that in prostate cancer‐free men, matched on birth year and county of residency. We used Cox regression to calculate the hazard ratios (HRs) for Alzheimer's and non‐Alzheimer's dementia (vascular dementia, dementia secondary to other diseases or unspecified dementias) for different types and duration of ADT and oral antiandrogens (AAs) as well as for men managed with WW. Results: A total of 25 967 men with prostate cancer and 121 018 prostate cancer‐free men were followed for a median of 4 years. In both groups 6% of the men were diagnosed with dementia. In men with prostate cancer, gonadotropin‐releasing hormone agonist treatment ( HR 1.15, 95% confidence interval [CI] 1.07–1.23) and orchiectomy (HR 1.60, 95% CI 1.32–1.93) were associated with an increased risk of dementia, as compared to no treatment in prostate cancer‐free men; however, this increase in risk was only observed for non‐Alzheimer's dementia and occurred from year 1–4 after start of ADT. No increase in risk for any type of dementia was observed for men treated with AAs or for men on WW. Conclusion: This population‐based cohort study does not support previous observations of an increased risk of Alzheimer's dementia for men on ADT; however, there was a small increase in risk of non‐Alzheimer's dementia.